2019
DOI: 10.15626/mp.2019.1723
|View full text |Cite
|
Sign up to set email alerts
|

A Negative Effect of a Contractive Pose is not Evidence for the Positive Effect of an Expansive Pose: Comment on Cuddy, Schultz, and Fosse (2018)

Abstract: Cuddy, Schultz and Fosse (2018) present the results of p-curve analyses that are interpreted as providing "clear evidential value for power posing effects”. This commentary highlights that the vast majority of the studies included in the p-curve analyses were not designed in a way that could speak to the efficacy of power poses relative to a normal or neutral pose. Further, I discuss how the few studies that were designed to shed light on this issue indicate that any overall effect of physical pose on feelings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Thus, for various previous pose (and posture) studies, it remained unclear whether the HPP/UP or the LPP/SP group was responsible for an effect. With respect to the effects of body positions on emotions, three studies (Rossberg‐Gempton & Poole, 1993; Veenstra et al, 2017; Zabetipour et al, 2015) indicated that the effect was driven by the SP or LPP condition, but many studies did not allow such a conclusion to be drawn (Credé, 2019). Thus, we recommend that studies use control groups in three‐cell designs in future research on poses and postures.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for various previous pose (and posture) studies, it remained unclear whether the HPP/UP or the LPP/SP group was responsible for an effect. With respect to the effects of body positions on emotions, three studies (Rossberg‐Gempton & Poole, 1993; Veenstra et al, 2017; Zabetipour et al, 2015) indicated that the effect was driven by the SP or LPP condition, but many studies did not allow such a conclusion to be drawn (Credé, 2019). Thus, we recommend that studies use control groups in three‐cell designs in future research on poses and postures.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…In fact, several authors have argued that effects on self‐reports may be driven by demand effects (Credé, 2019; Jansen & Hornbæk, 2018; Kozak et al, 2014; Simmons & Simonsohn, 2017). However, Carney et al (2015) argued that studies most often found effects when credible cover stories were used so that participants could not guess the research question—which suggests that demand characteristics might not be the driving force behind the phenomenon.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, without including a neutral control condition in such experiments, it cannot be determined whether the detected effect is caused by the presence of an expansive display or the absence of a contractive display or vice versa. This point was first mentioned by Credé (2018), who argued that a negative effect of a contractive display should not be taken as evidence for the positive effect of an expansive display. None of the syntheses mentioned above have compared contractive and expansive displays with neutral displays; thus, whether the presence of expansive displays or the absence of contractive displays is responsible for the affective and behavioral effects detected remains undetermined.…”
Section: Comparisons Of Bodily Displaysmentioning
confidence: 99%
“…The originally hypothesized effects, which are the hypothesized effects in the primary studies by the original authors, were not always equivalent to the relevant effects for this meta-analysis as the former could contain specific interactions with other variables (e.g., other manipulations) that could deactivate or even reverse the goal contagion effect. Therefore, both effects have to be clearly distinguished to avoid certain effects being falsely attributed to GC alone (for a recent example of such a case see Crede, 2019, in response to Cuddy, Schultz, & Fosse, 2018). P-and Z-values for these effects were extracted for additional publication bias tests and power estimations (Schimmack & Brunner, 2017.…”
Section: Originally Hypothesized Effectsmentioning
confidence: 99%